نركال: إله وملك العالم الأسفل - علي، ختام عدنان (الجامعة المستنصرية - كلية الآداب, 2017)
يشغل موضوع الموت وعالم الأموات جانبا مهما في تفكير الإنسان لأنه يعالج مشكلة أساسية من مشاكل الوجود لأن أي عمل يقوم به الإنسان كان للدين تأثير كبير فيه فكان لكل شخص إله خاص به يعبده ويقدم له القرابين من أجل الحصول على مرضاته. إذ كان الموت منذ أقدم العصور في تاريخ الإنسان أهمية خاصة في فكره كون الموت حتمية مطلقة لا خلاص منه، لتعلقه بوجود الإنسان ومصيره فكان من البديهي أن لا ينظر إليه على أنه نهاية مطلقة للحياة بل هناك حياة أخرى تعرف لدى سكان العراق القديم وهو "عالم ما بعد الموت"، ومن هنا توالت الأفكار عن خلود الروح والحياة الأخرى والبعث وعلاقته بالحساب والثواب والعقاب. وقد تناولت في بحثي هذا الاله نركال باعتباره إله وملك العالم الأسفل وتطرقت فيه إلى أصل التسمية في ضوء النصوص المسمارية والهيئة البشرية للإله نركال وأهم رموزه بالإضافة إلى علاقته بالعالم الأسفل في ضوء النصوص والأساطير العراقية القديمة والمعابد التي خصصت لعبادته.
Occupies the subject of death and the world of the dead, an important aspect of human thinking because it addresses the fundamental problem of the problems exist, because any action by the man of religion was a significant effect in which each person was his own god worshiped by offering him Alqrabim for Ahadjsol over While he was dying since ancient times in human history, especially in the idea that death inevitable absolutely no salvation for any place of meet them importance, for attachment to the existence of man and his destiny was of Alipidaha not seen as an absolute life-end, here it is rolled ideas about the immortality of the soul and the life of other The Baath and its relationship to the account of reward and punishment. This machine has been dealt with in my research Nergal as a god and king of the world down and touched it continued to label the human body and the god Nergal and the most important symbols in addition to its relationship to the bottom of the world in the light of cuneiform texts and myths, temples devoted to worship.
Keywords: العراق القديم -- الآلهة العراقية القديمة -- الإله نركال -- العالم السفلي